EFEKTIVITAS KOMUNIKASI NON-VERBAL DI INSTAGRAM @OFFICIAL_UNESA TERHADAP TINGKAT PEMAHAMAN INFORMASI AKADEMIK MAHASISWA TUNARUNGU DI UNIVERSITAS NEGERI SURABAYA - Sigalingging, Anjelia; Vinda Maya Setianingrum (The Commercium, 2025)
The purpose of this study was to measure how effective non-verbal communication in Instagram @official_unesa is to improve the academic understanding of deaf students at Surabaya State University. The method used in this study is a survey method with a descriptive quantitative research approach which is a study that describes systematically, factually, and accurately the relationship between phenomena to be investigated. This study was conducted on deaf students at Surabaya State University. The survey was conducted by distributing Google forms to deaf students at Surabaya State University via Whatsapp chat and Instagram. The results of this study found that non-verbal communication in Instagram @official_unesa is significantly effective in improving the level of understanding of academic information of deaf students at Surabaya State University with a correlation of 11.4% and the remaining 88.6% is influenced by other variables outside the study. In accordance with the hypothesis that the researcher had previously made, non-verbal communication on Instagram is significantly effective in improving the level of understanding of deaf students at Surabaya State University.